Gas emissions during olive mill waste composting under static pile conditions. (February 2016) - Nasini, L.; De Luca, G.; Ricci, A.; Ortolani, F.; Caselli, A.; Massaccesi, L.; Regni, L.; Gigliotti, G.; Proietti, P.
Abstract: This study evaluated gas emissions and chemical parameters during olive mill waste and grape stalk composting for three consecutive years. Each year, a static pile was built, and gas emissions were measured by a stationary chamber custom built for this purpose. The instrument indicated a CO2 concentration that was always higher (ranging from 0.33 to 3.33%) in comparison to nearby atmospheric levels the trails, a high rate of NOx at the beginning of each trial (4.4, 5.9 and 3.9 mg Nm −3 in the first, second and third year, respectively) and limited emissions of aldehydes, ammonia, aliphatic amine and VOCs from the composting piles. The TOC concentration decreased by approximately 28% because of the oxidative phenomena typical of the aerobic process. The total N concentration increased slightly (by approximately 24%) during the process. The germination index reached 100% in the three piles, demonstrating the efficiency of the process both in terms of stability and maturity. The overall results indicate that composting the by-products from olive oil extraction and grape transformation leads to the production of a high quality soil organic amendment, even if the environmental impact due to gas emissions must be considered. Highlights: Olive mill waste was composted with grape stalks in a static pile. A new stationary chamber was built to determine the gases emitted from the pile. The main gas emissions during composting was CO2 and NOx. The final composts showed a good chemical and agronomical quality.